P184 'Smart inhaler' in routine clinic practise: Is there a role in mild and moderate asthma management?. (11th November 2022) - See, Y; Chow, E; Crooks, M; Robinson, M; Watkins, K; Turner, F; Thompson, J; Faruqi, S
Abstract : Objectives: Confirming adherence to therapy is recommended prior to escalating treatment regime in patients with asthma. This is usually based on patient report and prescription pick up rates. We report the utility of using 'smart' inhaler technology to objectively address adherence with inhaled therapy among patients with mild to moderate asthma. Methods: Consecutive consenting patients (age ≥ 18) adherent to therapy based on clinical assessment had their LABA/ICS combination inhaler/s switched over to budesonide/formoterol turbohaler (Symbicort) with sensor. A proportion of the patient advised to use Symbicort as maintenance and reliever therapy (MART) while others to use it as Non-MART. This commercially available treatment comes with a sensor that connects via Bluetooth to an app, which records every time the inhaler is used. Inhaler technique and the use of the app was taught by a specialist nurse and asthma metrics recorded. At 4 weeks, adherence data was reviewed; asthma control was reviewed; and ongoing follow up arranged. Results: Of the 26 patients (mean age 51, 16 females), 73% recorded dose concordance > 50%. There is a greater concordance in MART group in which 89% of patients recorded concordance > 50% whilst only 65% in non-MART group achieve the same level of concordance. Results depicted in table 1 . Conclusion: 'Smart' inhalers used in routine clinical practice may help in achieving better asthma control both by identifying sub-optimal adherence, which can then be addressed. However, smart inhaler use alone does not guarantee adherence and role of clinicians in monitoring concordance data and providing suitable education remains very important.